2005
DOI: 10.1007/s10508-005-7926-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Physical Health After Sex Reassignment Surgery

Abstract: A long-term follow-up study of 55 transsexual patients (32 male-to-female and 23 female-to-male) post-sex reassignment surgery (SRS) was carried out to evaluate sexual and general health outcome. Relatively few and minor morbidities were observed in our group of patients, and they were mostly reversible with appropriate treatment. A trend toward more general health problems in male-to-females was seen, possibly explained by older age and smoking habits. Although all male-to-females, treated with estrogens cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
240
2
16

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 318 publications
(281 citation statements)
references
References 36 publications
19
240
2
16
Order By: Relevance
“…Most studies point out the substantial risks of these surgeries (Horbach et al, 2015), whereas data collection via surveys obtained similarly high self-reported complication rates (Lawrence, 2006). The high number of satisfied respondents found in the present study is comparable to earlier studies (Bouman et al, 2016;Buncamper et al, 2015;De Cuypere et al, 2005;Horbach et al, 2015;Lawrence, 2003;Lawrence, 2006;Nelson, Whallett, & McGregor, 2009;Rehman et al, 1999;Smith et al, 2005;Weigert et al, 2013) and emphasizes the effectiveness of gender-affirming procedures. Yet, most treatment evaluation studies have collected data in a clinical setting, whereas the present study reports on a cohort that was surveyed in their home environment with limited dependence on clinicians (although the participants were invited through the clinics).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Most studies point out the substantial risks of these surgeries (Horbach et al, 2015), whereas data collection via surveys obtained similarly high self-reported complication rates (Lawrence, 2006). The high number of satisfied respondents found in the present study is comparable to earlier studies (Bouman et al, 2016;Buncamper et al, 2015;De Cuypere et al, 2005;Horbach et al, 2015;Lawrence, 2003;Lawrence, 2006;Nelson, Whallett, & McGregor, 2009;Rehman et al, 1999;Smith et al, 2005;Weigert et al, 2013) and emphasizes the effectiveness of gender-affirming procedures. Yet, most treatment evaluation studies have collected data in a clinical setting, whereas the present study reports on a cohort that was surveyed in their home environment with limited dependence on clinicians (although the participants were invited through the clinics).…”
Section: Discussionsupporting
confidence: 85%
“…Yet, most treatment evaluation studies have collected data in a clinical setting, whereas the present study reports on a cohort that was surveyed in their home environment with limited dependence on clinicians (although the participants were invited through the clinics). With regard to regret, similar to other studies (De Cuypere et al, 2005;Lawrence, 2006;Smith et al, 2005), only a few study participants reported feelings of regret, which was exclusively related to disappointment and not to the wish to detransition. Amongst the eight people who reported dissatisfaction or/and regret with GAS, both genders and most surgical procedures were represented.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Considering a possible role of testosterone in female sexual desire among the general population (3,4), the lack of ovarian androgen production and the effect of continuous oestrogen treatment on the production of sex hormone-binding globulin (SHBG) in transsexual women might lead to hypoactive sexual desire disorder (HSDD) due to low levels of free testosterone. Although an earlier study from our group showed decreased levels of free testosterone in a majority of transsexual women (8), the association between sexual desire and testosterone in this group remains to be examined. Considering the observation of sexual desire complaints in transsexual women, and the much debated (9, 10) high prevalence of a lack of sexual interest among women in the general population (25.6% in Northern European women (11)), it would be relevant to assess this prevalence in transsexual women.…”
Section: Introductionmentioning
confidence: 67%
“…As Lawrence (1999) points out, it is extremely difficult to assess such changes in individuals with a GID diagnosis, as they preoperatively might give information only to be admitted to hormonal and surgical treatment. However, there is no doubt that changes as to the preferred gender of sex partner do occur (De Cuypere et al, 2005;Lawrence, 2005;Schroder & Carroll, 1999; some 30 in a sample of more than 1,200 GID patients seen by F.P. ).…”
Section: Specifiersmentioning
confidence: 99%